Effects of surface texture on wetting - Chua, Jonathan Jun Hao (2018)
Wetting is a phenomenon which occurs when a droplet spreads out on a surface. The extreme behaviour of wetting, known as superhydrophilicity, has garnered much attention due to it’s many real-life applications it can be applied to. The degree of wetting of a surface can be improved through several methods. These methods include special chemical alteration and roughness alteration, with both changing the interfacial interactions amongst the 3 phases of matter involved in the system. Extensive research has been conducted to create superhydrophilic surfaces through the fabrication of micropillars, some including nanostructures sitting above the micropillars. The advantage of doing so is that it allows the study of the wetting effects in a controlled manner through the usage of theoretical approaches in this field. However, the spacing ratio of micropillars has never been a factor or variable done in these experiments before. Thus, this absence of research motivates this project, to find out if spacing ratio attributes to the degree of wetting on a surface.